High performance flame retardant robot cable material and method of making same

CN122810464APending Publication Date: 2026-09-25ECHU SPECIAL WIRE & CABLE KUNSHAN CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610643753.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-11
Publication Date
2026-09-25

AI Technical Summary

Technical Problem

但上述方法存在明显缺陷:机械性能提升方面,填充剂过量会降低材料柔韧性,纤维增强加工难度大、成本高,共混改性易出现材料相容性差的问题,阻燃性能提升方面,卤系阻燃剂燃烧释放有毒烟气、不环保,无卤阻燃剂添加量大会削弱机械性能,且阻燃效率难以满足高端场景需求,无法实现机械性能与阻燃性能的协同优化

Benefits of technology

1.阻燃性能优异:皮芯结构阻燃纤维的芯层采用APP与DOPO复合阻燃体系,形成磷-磷协同阻燃,皮层的纳米填料与芯层阻燃成分形成协同作用,同时层状磷酸锆起到物理阻隔和增强作用,显著提升材料的阻燃效率,且阻燃成分不易迁移,阻燃性能长期稳定;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122810464A_ABST
    Figure CN122810464A_ABST
Patent Text Reader

Abstract

The application relates to the field of flame-retardant materials, and particularly discloses a high-performance flame-retardant robot cable material and a preparation method thereof, which comprises the following raw materials in parts by weight: 50-100 parts of polyethylene, 0.01-10.0 parts of a crosslinking agent, 0.01-10 parts of an auxiliary crosslinking agent, 0.01-10 parts of an antioxidant, 1-5 parts of a compatilizer, and 0.01-50 parts of a skin-core structure flame-retardant fiber; the skin layer of the skin-core structure flame-retardant fiber is a polyimide loaded nano filler reinforcing phase, and the core layer is a polyvinyl alcohol loaded ammonium polyphosphate-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide composite flame-retardant phase. The flame-retardant material has high flame retardance and good mechanical performance, and is suitable for being used as a robot cable insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of flame-retardant materials, and more specifically, to a high-performance flame-retardant robot cable material and its preparation method. Background Technology

[0002] Cable insulation materials, especially those for robotic cables, must be adaptable to dynamic operating conditions involving high-frequency bending and torsion. They must possess excellent mechanical properties and flame retardancy to withstand millions of cable chain movements, preventing frequent deformation that could lead to sheath cracking and conductor exposure. They must also meet halogen-free, low-smoke, and flame-retardant standards to prevent flame spread and reduce the release of toxic fumes. This is crucial because industrial robots and service robots are often used in complex environments with high temperatures and numerous electrical sparks. Insufficient mechanical properties would shorten cable life and increase maintenance costs, while a lack of flame retardancy could easily cause fires, endangering equipment and personnel safety. Furthermore, they must comply with global environmental and safety standards. In existing technologies, mechanical performance improvement often involves adding inorganic fillers, fiber reinforcement, or polymer blending modification, while flame retardant performance improvement mainly relies on adding halogenated or halogen-free flame retardants. However, these methods have significant drawbacks: regarding mechanical performance improvement, excessive filler can reduce material flexibility; fiber reinforcement is difficult and costly to process; and blending modification is prone to poor material compatibility. Regarding flame retardant performance improvement, halogenated flame retardants release toxic fumes upon combustion, which is environmentally unfriendly; and large amounts of halogen-free flame retardants can weaken mechanical performance, and their flame retardant efficiency is insufficient to meet the demands of high-end applications, failing to achieve synergistic optimization of mechanical and flame retardant performance. As robots evolve towards higher precision, higher load capacity, and miniaturization, the comprehensive performance requirements for cable materials in high-end applications are becoming increasingly stringent. Existing materials are no longer adequate for the needs of humanoid and special-purpose robots, and high-end materials still rely partially on imports. Therefore, developing cable materials that combine excellent mechanical properties, high-efficiency flame retardancy, and environmental friendliness is urgently needed. Looking ahead, the global robot market continues to expand, and high-performance cable materials, as core components, can be widely used in industrial automation, medical, and logistics fields. This aligns with the national strategy of high-end manufacturing and domestic substitution, filling technological gaps and meeting market demands, resulting in significant economic and social benefits. Summary of the Invention

[0003] In order to provide a high flame retardant and high strength cable material, this application provides a high-performance flame retardant robot cable material and its preparation method.

[0004] In a first aspect, this application provides a high-performance flame-retardant robot cable material, comprising the following raw materials in parts by weight: 50-100 parts of polyethylene, 0.01-10.0 parts of crosslinking agent, 0.01-10 parts of co-crosslinking agent, 0.01-10 parts of antioxidant, 1-5 parts of compatibilizer, and 0.01-50 parts of core-sheath structure flame-retardant fiber. The sheath of the core-sheath structure flame-retardant fiber is a polyimide-supported nanofiller reinforcing phase, and the core is a polyvinyl alcohol-supported ammonium polyphosphate-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide composite flame-retardant phase.

[0005] The hydroxyl groups of polyvinyl alcohol in the core layer form hydrogen bonds with the phosphate groups of ammonium polyphosphate, and combine with the phosphorus-phenanthrene structure of DOPO through π-π stacking, ensuring a stable load of flame-retardant components. The polyimide skin layer is formed by the thermal imidization of polyamic acid. The conjugated structure of the imide ring imparts high mechanical strength. The decomposition of phosphorus-nitrogen flame retardants releases polyphosphoric acid, catalyzing the dehydration of PE and PI to form char and condensed phase flame retardancy. At the same time, NH3 and N2 are released to dilute combustible gases. DOPO decomposes to generate phosphorus-containing free radicals, which capture free radicals in the combustion chain reaction for gas-phase flame retardancy, forming condensed phase catalytic char formation and gas-phase free radical capture. The PI skin layer, as a heat-resistant skeleton, maintains structural integrity at high temperatures, providing support for the char layer. The compatibilizer promotes the uniform dispersion of core-shell fibers in the PE matrix, forming a continuous three-dimensional network of fibers, which plays a reinforcing role in the skeleton. The PE cross-linked network firmly fixes the fibers, preventing fiber slippage under stress, achieving mechanical synergy between the flexible matrix and rigid fibers. At the same time, the thermal stability of cross-linked PE is improved, complementing the flame-retardant properties of the fibers.

[0006] Preferably, the core layer of the flame-retardant fiber with a core-sheath structure comprises the following raw materials in parts by weight: 8-12 parts of polyvinyl alcohol, 3-8 parts of ammonium polyphosphate, 1-5 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 60-100 parts of N,N-dimethylformamide, and 0.1-2.0 parts of dispersant; and the sheath comprises the following raw materials in parts by weight: 12-20 parts of polyamic acid, 1-5 parts of nanofiller, 60-90 parts of N,N-dimethylformamide, and 0.1-2.0 parts of coupling agent.

[0007] The core-sheath structure flame-retardant fiber is rich in flame-retardant components and has a good flame-retardant effect. Polyamic acid and nanofillers are bonded together by a coupling agent, which makes the nanofillers uniformly dispersed in the sheath, improving the mechanical strength of the sheath and enhancing its flame-retardant and barrier properties. The hydroxyl groups of polyvinyl alcohol in the core layer and the carboxyl groups of polyamic acid in the sheath form hydrogen bonds, forming a stable bonding layer at the core-shell interface and preventing core-shell separation. At the same time, the dense structure of the sheath protects the core layer, and the flame-retardant components in the core layer play a flame-retardant role. Together, they improve the overall performance of the flame-retardant fiber and optimize the flame-retardant and mechanical effects of the material as a whole.

[0008] Preferably, the shell structure flame-retardant fiber is obtained by coaxial electrospinning. The voltage of the coaxial electrospinning process is 15-22kV, the core layer feeding speed is 0.3-0.5mL / h, the skin layer feeding speed is 0.8-1.0mL / h, the distance between the spinneret and the receiving roller is 12-15cm, the receiving roller speed is 300-500r / min, the ambient temperature is 25±10℃, and the relative humidity is 40%±20%.

[0009] When the core voltage is too low, the spinning solution is insufficiently stretched, resulting in low molecular chain orientation, uneven core-sheath structure thickness, and weak hydrogen bonding between the core and sheath layers. When the voltage is too high, the spinning solution is overstretched, leading to fiber breakage, excessively fine fiber diameter, and easy damage to the sheath layer. It may also cause agglomeration of the flame-retardant components in the core layer and disrupt hydrogen bonding. This voltage range allows for moderate stretching of the spinning solution, orderly orientation of the molecular chains along the spinning direction, and tight hydrogen bonding between the core and sheath layers, forming a regular core-sheath structure, further enhancing hydrogen bonding. A core layer feed rate lower than the sheath rate ensures complete sheath coverage of the core layer, preventing core exposure. Excessive feed rate results in excessive spinning solution supply, excessively coarse fiber diameter, low molecular chain orientation, poor sheath density, and insufficient chemical bonding between the coupling agent, polyamic acid, and nanofillers. Insufficient feed rate leads to insufficient spinning solution supply, resulting in fiber breakage and an incomplete core-sheath structure. This speed ratio ensures a reasonable core-shell thickness ratio, a dense cortex, stable core load, and sufficient intermolecular hydrogen and chemical bonding. If the spinneret is too close to the receiving roller, the spinning solution's flight time is insufficient, the solvent does not fully evaporate, the molecular chain orientation is low, the core-shell interface is not tightly bonded, and core-shell separation is likely. If the distance is too far, the spinning solution is easily affected by the environment, resulting in uneven fiber diameter, easy molecular chain breakage, and weakened hydrogen bonding. This distance range ensures sufficient stretching of the spinning solution, initial solvent evaporation, ordered molecular chain orientation, and stable hydrogen bonding at the core-shell interface. If the receiving roller speed is too low, the fiber collection is loose, the molecular chain orientation is low, and the inter-fiber bonding is weak. If the speed is too high, the fiber is subjected to excessive centrifugal force, making it prone to breakage or over-orientation, leading to fiber embrittlement and damage to the imide bonds in the cortex. This speed range ensures tight fiber collection and reasonable molecular chain orientation, guaranteeing the fiber's mechanical properties without damaging the molecular structure and chemical bonds.

[0010] The core spinning solution and the sheath spinning solution come into contact at the spinneret exit. The hydroxyl groups of polyvinyl alcohol in the core layer and the carboxyl groups of polyamic acid in the sheath layer form hydrogen bonds, achieving initial bonding at the core-shell interface and forming a core-sheath structure fiber. During the drying process, the solvent evaporates, increasing the hydrogen bond density between the molecular chains of the core and sheath layers, resulting in a denser fiber structure. During heat setting, the polyamic acid in the sheath layer undergoes dehydration and transformation, enhancing the rigidity of the molecular chains. Simultaneously, the chemical bonds between the coupling agent, polyamic acid, and nanofillers are further stabilized, and the nanofillers form a tighter bond with the PI molecular chains. The hydrogen bonds between the hydroxyl groups of polyvinyl alcohol in the core layer and APP and DOPO are further strengthened, ensuring a stable load of flame-retardant components. The resulting core-sheath structure flame-retardant fiber has a reasonable core-shell thickness ratio, a dense and non-porous sheath, and a uniformly dispersed core layer with ordered molecular chain orientation, ensuring consistent performance of each fiber and thus guaranteeing a good overall flame-retardant effect.

[0011] Preferably, the polyethylene melt flow rate is 1-3 g / 10 min, the degree of polymerization of the polyvinyl alcohol is 1750±150, and the degree of polymerization of the ammonium polyphosphate is n≥1000.

[0012] Polyethylene has a moderate MFR (Medium-to-Flat Rate) and can be uniformly mixed with core-shell flame-retardant fibers. Under the action of compatibilizers, the polyethylene molecular chains and the PI (polyethylene) skin layer of the core-shell fiber form a stable bond. At the same time, the linear structure of polyethylene and the cross-linking system work together to form a three-dimensional network structure, which disperses the stress on the core-shell fiber and improves the mechanical properties of the material. The flame-retardant effect of the core-shell fiber and the processing performance of polyethylene are suitable, ensuring that the material is easy to process and has excellent flame-retardant effect.

[0013] Preferably, the nanofiller includes: flame retardant intercalated layered zirconium phosphate, wherein the flame retardant includes one or both of nitrogen-based and phosphorus-based flame retardants.

[0014] Layered zirconium phosphate provides a stable intercalation carrier for flame retardants. The flame retardant binds to the layered zirconium phosphate through hydrogen bonds or chemical bonds, preventing flame retardant migration. The layered structure may also form certain protrusions, which further form a locking structure with a certain degree of mobility by connecting the interwoven fibers in the system to form a network reinforcement structure. At the same time, the flame retardant intercalation into the layered zirconium phosphate not only physically blocks heat and oxygen through the layered structure, but also releases phosphoric acid as a secondary acid source, forming a dual acid catalytic system with APP's polyphosphoric acid, accelerating the formation of a dense carbon layer, which is more complete than the single acid source for carbon formation.

[0015] Preferably, the mass ratio of the flame retardant intercalated layered zirconium phosphate to polyamic acid is 1:(4-6).

[0016] This mass ratio is more suitable for the flame-retardant components in the core layer, further achieving the best performance in flame retardancy and reinforcement.

[0017] Preferably, the mass ratio of core-sheath structure flame-retardant fiber to polyethylene is 1:(7-11).

[0018] Secondly, this application provides a method for preparing a high-performance flame-retardant robot cable material, comprising the following steps: weighing raw materials by mass, mixing components other than crosslinking agent and co-crosslinking agent, heating and stirring to obtain a premix, adding crosslinking agent and co-crosslinking agent, extruding, cooling, and obtaining a high-performance flame-retardant robot cable material.

[0019] Thirdly, this application provides a robot cable, comprising a stranded conductor layer, an insulation layer, an aramid yarn filling layer, a wrapping tape, a nickel-plated wire / copper foil braided layer, and a sheath layer, wherein the insulation layer material is prepared using the above-mentioned high-performance flame-retardant robot cable material or the preparation method of the above-mentioned high-performance flame-retardant robot cable material.

[0020] In summary, this application has the following beneficial effects: 1. Excellent flame retardant performance: The core layer of the core-sheath structure flame retardant fiber adopts the APP and DOPO composite flame retardant system to form a phosphorus-phosphorus synergistic flame retardant. The nanofiller in the sheath layer and the flame retardant components in the core layer form a synergistic effect. At the same time, the layered zirconium phosphate plays a physical barrier and reinforcement role, which significantly improves the flame retardant efficiency of the material. Moreover, the flame retardant components are not easy to migrate, and the flame retardant performance is stable in the long term. 2. Excellent mechanical properties: The sheath of the flame-retardant fiber in the core-sheath structure is reinforced with polyimide-loaded nanofiller, which has excellent mechanical strength and wear resistance, effectively protecting the core layer and meeting the needs of frequent bending in robot cables; 3. Good compatibility and processing performance: The PI sheath of the core-sheath structure flame retardant fiber has good compatibility with the polyethylene matrix, avoiding problems such as blooming and cracking caused by poor compatibility between traditional flame retardants and polyethylene; at the same time, the polyethylene is selected with a specific melt flow rate model and a reasonable preparation process, so that the material has good melt flowability and processing stability, and can be prepared by conventional extrusion process, which is easy to mass-produce. Attached Figure Description

[0021] Figure 1 : A diagram of the robot cable structure of this invention. Detailed Implementation

[0022] To further aid in understanding the technical solution of the present invention, several specific embodiments are provided to describe the technical solution of the present invention in a more detailed manner. All described embodiments are only some embodiments of the present invention, not all of them. Embodiments can be combined with each other, and the same or similar concepts or processes may not be repeated in some embodiments. The following embodiments are further illustrations of the present invention, but the present invention is not limited thereto.

[0023] The components used in the preparation examples in this application refer to those obtained through the preparation methods described in the examples. Unless otherwise specified, the experimental reagents are all from commercially available brands or obtained through conventional preparation methods.

[0024] Polyethylene was purchased from PetroChina Daqing Petrochemical HDPE5000S; polyvinyl alcohol was purchased from Chengjian Polyvinyl Alcohol 1788; ammonium polyphosphate was purchased from Langbowan APP-1000; layered zirconium phosphate was purchased from Wuhan Maikairui Chemical Co., Ltd. (mkrD50 < 2µm); melamine cyanurate (MCA) was purchased from Dongguan Hongtaiji Flame Retardant Materials Co., Ltd.; crosslinking agent (dicumyl peroxide DCP, industrial grade, 98% purity); co-crosslinking agent (traceryl isocyanurate TAIC, industrial grade). Antioxidant (hindered phenol 1010, industrial grade); compatibilizer (maleic anhydride-grafted polyethylene MAH-g-PE); polyamic acid purchased from Merck Pyre-ML®RC-5097; 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO, industrial grade, 99% purity); N,N-dimethylformamide (DMF, analytical grade); dispersant (polyethylene glycol PEG-400, analytical grade); coupling agent (KH550, industrial grade). Preparation Example

[0025] Preparation Example 1: Flame Retardant Intercalated Layered Zirconium Phosphate Weigh layered zirconium phosphate and melamine cyanurate at a mass ratio of 3:1; separately weigh deionized water (20 times the total mass of layered zirconium phosphate and MCA), coupling agent KH550 (2% of the mass of layered zirconium phosphate), and PEG-400. Layered zirconium phosphate was added to deionized water and ultrasonically dispersed for 30 min (ultrasonic power 300 W, ultrasonic frequency 40 kHz). Coupling agents KH550 and PEG-1750 were added, the temperature was raised to 50℃, and the mixture was stirred for 1 h at a stirring speed of 200 r / min. Melamine cyanurate was added, the temperature was raised to 80℃, and the mixture was stirred at a constant temperature for 4 h at a stirring speed of 300 r / min. The mixture was then vacuum filtered at a pressure of 0.08 MPa to obtain a filter cake. The filter cake was washed three times with deionized water until the washing liquid was neutral. The washed filter cake was placed in a forced-air drying oven and dried at 105℃ for 6 h. After drying, the cake was pulverized and passed through a 200-mesh sieve to obtain a white powdery flame retardant intercalated layered zirconium phosphate.

[0026] Preparation Example 2: Flame Retardant Intercalated Layered Zirconium Phosphate The only difference between this preparation example and Preparation Example 1 is that the PEG used is PEG-400.

[0027] Preparation Example 3: Flame-retardant Fiber with Sheath-Core Structure Weigh the core layer raw materials according to the following weight parts: 10 parts polyvinyl alcohol, 5 parts APP, 3 parts DOPO, 80 parts DMF, and 1.0 part dispersant; add the above raw materials to a three-necked flask, heat to 70°C, stir for 3 hours (stirring speed 300 r / min) until the raw materials are completely dissolved, let stand for 1.5 hours to degas, and obtain the core layer spinning solution; Weigh the following raw materials by weight: 16 parts PAA, 3.2 parts of flame retardant intercalated layered zirconium phosphate prepared in Preparation Example 1, 75 parts DMF, and 1.0 part coupling agent; add the above raw materials to another three-necked flask, heat to 60°C, stir for 2 hours at a stirring speed of 250 r / min, and let stand for 1.5 hours to remove bubbles to obtain the skin spinning solution; The core spinning solution and the sheath spinning solution were loaded into syringes and connected to coaxial spinnerets. The inner core diameter of the coaxial spinneret was 0.5 mm and the outer shell diameter was 1.2 mm. Electrospinning was performed according to the following parameters: voltage 18 kV, core layer feed rate 0.4 mL / h, sheath layer feed rate 0.9 mL / h, distance between spinneret and receiving roller 13.5 cm, receiving roller speed 400 r / min, ambient temperature 25℃, and relative humidity 40%. The spun fiber membrane was collected and placed in a forced-air drying oven and dried at 60℃ for 3 h. Then it was placed in a muffle furnace and heated and set at 220℃ for 1.5 h. Preparation Example 4: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the weight parts of the skin material: 16 parts PAA, 2 parts of flame retardant intercalated layered zirconium phosphate obtained in preparation example 1, 75 parts DMF, and 1.0 part coupling agent.

[0028] Preparation Example 5: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the weight parts of the skin material: 16 parts PAA, 5 parts of the flame retardant intercalated layered zirconium phosphate obtained in preparation example 1, 75 parts DMF, and 1.0 part coupling agent.

[0029] Preparation Example 6: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the outer layer material: 16 parts PAA, 3.2 parts of flame retardant intercalated layered zirconium phosphate obtained in preparation example 2, 75 parts DMF, and 1.0 part coupling agent.

[0030] Preparation Example 7: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the electrospinning voltage of 10kV.

[0031] Preparation Example 8: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the raw material for the outer layer: 16 parts PAA, 3.2 parts layered zirconium phosphate, 75 parts DMF, and 1.0 part coupling agent.

[0032] Preparation Example 9: Core-Sheet Structure Flame-Retardant Fiber The only difference between this preparation example and preparation example 2 is the raw material for the outer layer: 16 parts PAA, 3.2 parts flaky mica powder, 75 parts DMF, and 1.0 part coupling agent. Example Example 1

[0033] Weigh the raw materials by weight: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber prepared in Example 3.

[0034] Preparation steps: Add PE, antioxidant 1010, MAH-g-PE and F1 to a high-speed mixer, heat to 110℃, stir for 1.5h (stirring speed 400r / min), and after mixing evenly, obtain the premix; The premixed material was added to a twin-screw extruder and heated to 165°C. After melting and plasticizing, DCP and TAIC were added, and stirring was continued for 0.7 hours. The mixture was then extruded through an extruder at a speed of 15 r / min, cooled and shaped, with the thickness controlled at 0.3 mm and the cooling water temperature at 25°C, to obtain a high-performance flame-retardant robot cable material.

[0035] High-performance flame-retardant robot cable material is extruded onto the stranded conductor layer to form an insulation layer; aramid yarn is wound around the insulation layer to form a filler layer; flame-retardant non-woven fabric wrapping tape is wrapped around the filler layer; then nickel-plated wire is used to braid the layer to form a braided layer; finally, a flame-retardant sheath is extruded over the braided layer, and the robot cable is obtained by traction and winding. Example 2

[0036] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 100 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 3. Example 3

[0037] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 4. Example 4

[0038] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 5. Example 5

[0039] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 6. Example 6

[0040] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 7. Example 7

[0041] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 8. Example 8

[0042] The only difference between this embodiment and Example 1 is that the raw materials weighed by weight are: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, and 8 parts of the core-sheath structure flame-retardant fiber obtained in Preparation Example 9. Comparative Example 1:

[0043] Raw materials weighed by weight: 75 parts PE, 3.0 parts crosslinking agent DCP, 3.0 parts co-crosslinking agent TAIC, 5.0 parts antioxidant 1010, 3 parts MAH-g-PE, 3 parts modified APP, 2 parts DOPO, and 2 parts commercially available PI fiber.

[0044] Preparation steps: Add PE, antioxidant 1010, MAH-g-PE and F1 to a high-speed mixer, heat to 110℃, stir for 1.5h (stirring speed 400r / min), and after mixing evenly, obtain the premix; The premixed material was added to a twin-screw extruder and heated to 165°C. After melting and plasticizing, DCP and TAIC were added, and stirring was continued for 0.7 hours. The mixture was then extruded through an extruder at a speed of 15 r / min and cooled and shaped at a cooling water temperature of 25°C to obtain a high-performance flame-retardant robot cable material. Performance testing

[0045] Test 1: The flame retardancy rating of the product is tested according to the standard UL94. Test 2: Test the oxygen index of the product according to the standard GB / T2406; Test 3: The tensile strength of the product is tested according to the standard GB / T1040, with a tensile speed of 50 mm / min.

[0046] The test results are shown in Table 1.

[0047] Table 1

[0048] Performance analysis, combined with comparative examples and Table 1, shows that; 1. Regarding flame retardant performance: The flame retardant materials used in Examples 1-8 and the corresponding robot cables all exhibit significantly better flame retardant performance than Comparative Example 1. Combined with the performance summary table, it can be seen that Example 1 has an oxygen index of 33.4% and a flame retardant rating of UL94V-0, while Comparative Example 1 (DM1) has an oxygen index of only 17.1% and a flame retardant rating of only V-2, a significant difference. This fully demonstrates that the core-sheath structure flame retardant fiber specified in this application, through the synergistic phosphorus-nitrogen-carbon flame retardant effect of the core layer APP-DOPO and the sheath flame retardant intercalated layered zirconium phosphate, can achieve… This effectively solves the problems of agglomeration and poor compatibility when ordinary flame retardants (APP+DOPO) are directly added, and significantly improves the flame retardant effect. Further, combined with Examples 3-5 and 7-8, it can be seen that the amount and type of intercalated layered zirconium phosphate in the cortex flame retardant directly affect the flame retardant performance. Example 7 confirms that the phosphorus-nitrogen synergistic effect of the cortex intercalated flame retardant is the key to achieving excellent flame retardant performance. Example 6 shows that the preparation process of the core-shell fiber (electrospinning voltage) also affects the flame retardant performance. Only core-shell fibers with complete structure can better achieve synergistic flame retardancy.

[0049] 2. Mechanical properties: The performance summary table shows that the tensile strength of the flame-retardant materials in Examples 1-8 is above 17.4 MPa, and the elongation at break is above 270%, while the tensile strength of Comparative Example 1 is only 12.8 MPa, showing a significant difference. This indicates that the core-shell structure flame-retardant fiber of this application can not only improve flame-retardant performance, but also play a reinforcing role and improve the mechanical properties of the material. In Example 4, excessive flame retardant may lead to a decrease in the local agglomeration and dispersion of the fiber, and reduce the physical interlocking of the surface rough nodes. Example 5 confirms the optimizing effect of the type of dispersant on fiber dispersion and material mechanical properties. In Example 6, insufficient spinning voltage and imperfect fiber structure significantly weaken its reinforcing effect, further highlighting the rationality of the core-shell fiber preparation process parameters of this application.

[0050] The specific embodiments described herein are merely illustrative of this application and are not intended to limit it. Those skilled in the art can make modifications to these embodiments without contributing any inventive step after reading this specification, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A high-performance flame-retardant robot cable material, characterized in that: The raw materials include the following parts by weight: 50-100 parts of polyethylene, 0.01-10.0 parts of crosslinking agent, 0.01-10 parts of co-crosslinking agent, 0.01-10 parts of antioxidant, 1-5 parts of compatibilizer, and 0.01-50 parts of core-sheath structure flame-retardant fiber. The sheath of the core-sheath structure flame-retardant fiber is a polyimide-supported nanofiller reinforcing phase, and the core is a polyvinyl alcohol-supported ammonium polyphosphate-9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide composite flame-retardant phase.

2. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The core layer of the flame-retardant fiber structure comprises the following raw materials in parts by weight: 8-12 parts of polyvinyl alcohol, 3-8 parts of ammonium polyphosphate, 1-5 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, 60-100 parts of N,N-dimethylformamide, and 0.1-2.0 parts of dispersant. The outer layer comprises the following raw materials in parts by weight: 12-20 parts of polyamic acid, 1-5 parts of nanofiller, 60-90 parts of N,N-dimethylformamide, and 0.1-2.0 parts of coupling agent.

3. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The core-sheath structure flame-retardant fiber includes the following preparation steps: weighing the core layer raw material according to the mass fraction, heating and stirring, letting it stand to degas, obtaining the core layer spinning solution; weighing the core layer raw material according to the mass fraction, heating and stirring evenly, letting it stand to degas, obtaining the sheath spinning solution; coaxially electrospinning the spinning solution into shape, drying, and heating to set, thus obtaining the core-sheath structure flame-retardant fiber.

4. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The core-sheath structure flame-retardant fiber is obtained by coaxial electrospinning. The voltage of the coaxial electrospinning process is 15-22kV, the core layer pushing speed is 0.3-0.5mL / h, the sheath layer pushing speed is 0.8-1.0mL / h, the distance between the spinneret and the receiving roller is 12-15cm, the receiving roller speed is 300-500r / min, the ambient temperature is 25±10℃, and the relative humidity is 40%±20%.

5. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The polyethylene melt flow rate is 1-3 g / 10 min, the polyvinyl alcohol degree of polymerization is 1750±150, and the ammonium polyphosphate degree of polymerization n≥1000.

6. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The nanofiller includes: flame retardant intercalated layered zirconium phosphate, wherein the flame retardant includes one or both of nitrogen-based and phosphorus-based flame retardants.

7. The high-performance flame-retardant robot cable material according to claim 6, characterized in that: The mass ratio of the flame retardant intercalated layered zirconium phosphate to polyamic acid is 1:(4-6).

8. The high-performance flame-retardant robot cable material according to claim 1, characterized in that: The mass ratio of the core-sheath structure flame-retardant fiber to polyethylene is 1:(7-11).

9. A method for preparing a high-performance flame-retardant robot cable material according to any one of claims 1-8, characterized in that: Includes the following steps: Weigh the raw materials according to the mass fraction, mix the components except for the crosslinking agent and the co-crosslinking agent, heat and stir to obtain a premix, add the crosslinking agent and the co-crosslinking agent, extrude, cool, and obtain a high-performance flame-retardant robot cable material.

10. A robot cable, characterized in that, It includes a stranded conductor layer, an insulation layer, an aramid yarn filling layer, a wrapping tape, a nickel-plated wire / copper foil braided layer, and a sheath layer. The insulation layer material includes the high-performance flame-retardant robot cable material according to any one of claims 1-8, and / or the insulation layer material is prepared by the preparation method of the high-performance flame-retardant robot cable material according to claim 9.